2018
DOI: 10.3390/nu10060691
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fermented by Specific Lactobacillus Strains Regulates the Serum Levels of IL-6, TNF-α and IL-10 Cytokines in a LPS-Stimulated Murine Model

Abstract: Studies report that metabolites, such as peptides, present in fermented milk with specific lactic acid bacteria, may regulate cytokine production and exert an anti-inflammatory effect. Hence, the cytokine regulatory effect of fermented milk by specific Lactobacillus strains was evaluated in a lipopolysaccharide (LPS)-stimulated murine model. From twelve strains, three (J20, J23 and J28) were selected for their high proteolytic and acidifying capacities in milk and used for the in vivo study. Three treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…The reduced level of IL-6 among patients who consumed probiotic in our clinical trial translated similar findings in the recent experimental study on Lactobacillus fermentum J20, J23 and J28 in a murine model [26]. Interestingly, we observed similar findings among recruited patients who consumed placebo.…”
Section: Discussionsupporting
confidence: 90%
“…The reduced level of IL-6 among patients who consumed probiotic in our clinical trial translated similar findings in the recent experimental study on Lactobacillus fermentum J20, J23 and J28 in a murine model [26]. Interestingly, we observed similar findings among recruited patients who consumed placebo.…”
Section: Discussionsupporting
confidence: 90%
“…The strains Lactobacillus fermentum J20 and J28, previously isolated from Mexican artisanal cheese, were selected on the basis that these bacteria have already exhibited both technological and probiotic potential [18], conjugated linoleic acid [19], and anti-inflammatory and immunomodulatory properties, by using models of colon inflammation with LPS [20] or Dextran Sulfate Sodium (DSS) [21], and healthy Wistar rats [18], respectively. Bacteria were grown in MRS (De Man, Rogosa, and Sharpe, Difco) broth (12 h, 37 °C).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Kanmani and Kim 16 reported that several types of lactic acid bacteria attenuated LPS induced negative regulators (A20, Tollip and SIGIRR) and pro-inflammatory cytokines (IL-6 and TNF-α) in HepG2 cells at 12 h, but not significantly altered the mRNA expression of TLR2 and TLR4. Additionally, Lactobabillus strains FM also found to suppress TNF-α and IL-6 expression in a LPS-infected murine model 63 .…”
Section: Discussionmentioning
confidence: 93%